Գրաբարի բառարաններում չարձանագրված դարձվածքներ Ղազար Փարպեցու «Պատմութիւն Հայոց» երկում - Հարությունյան, Քնար (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Изучение древнеармянских фразеологизмов имеет относительно небольшую историю, и некоторые вопросы еще не решены окончательно. Один из них – вопрос фразеологизмов, не представленных в словарях. Исследование лексики труда §История Армении¦ историка V века Лазаря Парпеци выявило 29 новых фразеологизмов, не вошедших ни в фразеологический, ни в другие словари древнеармянского языка. The study of Old Armenian (Grabar) idioms has got a comparatively short history, so there are some questions which have not been solved conclusively. One of them is the problem of the idioms not recorded in the dictionaries. The study of the vocabulary of “History of Armenia” by the 5th century historian Ghazar Parphetsi revealed 29 new idioms not included in either the phraseological or other dictionaries of the Old Armenian language.
Keywords: Բառարանագիտություն; Բառարաններ